Some Thoughts on the Future of Research in Crime and Delinquency - Witte, Ann Dryden (Journal of research in crime and delinquency, 1993)
The author believes that there is a need to narrow the theoretical perspective used for research on crime and delinquency in some ways. Traditional research on crime and delinquency takes the law and societal institutions as given. Yet the law and our governmental social, and economic institutions form the context within which crime and delinquency occur. They set the stage for crime and delinquency. Policy-relevant theory must study the stage as well as the action that takes place on it. As social scientists, they need to study the structure of law and understand the sources of support for law abidingness. They require a broad perspective that studies the stage on which crime takes place, the law and its administration, as well as offenders and the offenses they commit. Experiments and longitudinal studies of high-risk groups are likely to be most productive. They can improve the understanding of crime and delinquency and beneficially inform policymaker. Coordination and cooperation are central to carrying out a productive research agenda on crime and delinquency. Experiments and longitudinal analyses are expensive and require long-term commitments by funding agencies and researchers. To ensure adequate and continuous funding, public and private organizations need to fund jointly and make long-term commitments. Productive research also requires the cooperation of many public and private agencies particularly criminal justice agencies. Finally, the research requires the cooperation and support of the citizens who are being studied